2016
DOI: 10.4103/2231-0746.186120
|View full text |Cite
|
Sign up to set email alerts
|

The use of superficial cervical plexus block in oral and maxillofacial surgical practice as an alternative to general anesthesia in selective cases

Abstract: Aim:(1) To assess the feasibility, safety, and effectiveness of superficial cervical plexus (SCP) block in oral and maxillofacial surgical (OMFS) practice as an alternative to general anesthesia in selective cases. (2) To assess any associated complication specifically related to the procedure.Subjects and Methods:The total number of patients was 10, out of which 6 were male and 4 were female patients. Six patients had incision and drainage of perimandibular space infections, two patients had Level Ib cervical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 6 publications
1
10
0
3
Order By: Relevance
“…SCP block takes care of the pain in skin incision and the necessary tissue dissection. By combining SCP block with conventional nerve blocks such as the inferior alveolar and long buccal nerve blocks, good anesthesia and positive outcomes were achieved as was seen by Kamal Kanthan [2] in a study of 10 patients. Arun [7] used this block in drainage of Ludwig's angina and concluded that superficial cervical plexus block permits the surgical decompression in their case and in a rural hospital with limited resources, it should be considered as an option.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…SCP block takes care of the pain in skin incision and the necessary tissue dissection. By combining SCP block with conventional nerve blocks such as the inferior alveolar and long buccal nerve blocks, good anesthesia and positive outcomes were achieved as was seen by Kamal Kanthan [2] in a study of 10 patients. Arun [7] used this block in drainage of Ludwig's angina and concluded that superficial cervical plexus block permits the surgical decompression in their case and in a rural hospital with limited resources, it should be considered as an option.…”
Section: Discussionmentioning
confidence: 78%
“…The downside of GA is high economic cost, a number of highly trained personnel, morbidity, mortality, and high-cost equipment. The advantage of regional anesthesia includes stress-free anesthesia as it prevents high catecholamine release, lower rate of blood loss because of local vasoconstrictors and sympathetic blockade, easy-to-perform techniques, and lower morbidity rates in appropriate dosages of local anesthesia (LA) [2]. Cervical plexus block (CPB) was first performed by Halstead in 1884 at Bellevue, and later, Kappis in Germany described the posterior route.…”
Section: Introductionmentioning
confidence: 99%
“…13 Shteif et al, reported three cases with submandibular and submental abscess drained under SCPB in combina on with 6 trigeminal V3 nerve block. Kanthan KR, used SCPB in 10 pa ents, out of which six pa ent had perimandibular space infec ons, two pa ent had Level Ib node biopsies, one pa ent had enuclea on of cyst in the body of mandible, one pa ent had open reduc on internal fixa on of isolated 14 angle fracture. All these studies reported high success rate with low complica on and be er pa ent acceptance.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasound-guided bilateral cervical plexus blocks could be performed for postoperative analgesia following thyroid surgeries [ 22 ]. In oral and maxillofacial surgical practice and in selected neck surgeries, use of superficial cervical plexus blocks was offered as an alternative to general anesthesia [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%